An Extended Evaluation of Academic Encouragement Scale for Adolescents. (June 2021) - Mu, Wenlong; Chen, Zheng; Duan, Wenjie
The Academic Encouragement Scale (AES) evaluates academic encouragement received from someone whom the student respects. This study reported the psychometric properties of the AES among 1602 Chinese adolescents. The results of confirmatory factor analysis (CFA) supported a two-factor structure of the AES (i.e., challenge-focused encouragement (CFE) and potential-focused encouragement). Multigroup CFA indicated that the AES showed measurement and structural invariance across gender groups. Each factor of the AES showed adequate internal consistency reliability ( α > .84) and test–retest stability ( r > .75). Correlation analyses demonstrated that the AES subscales were significantly related to academic self-efficacy, hope, and social connectedness in the expected directions, which yielded evidence for the concurrent validity of the AES. Results indicated that the CFE factor significantly predicted academic achievement, but the potential-focused encouragement factor did not significantly predict academic achievement. Overall, the findings support the use of the AES among adolescents.